Intercovery Siam Orange Plants with Seasonal Plants using The Leisa System - N. P. A Sulistiawati; N.K.A Astiari; K.Agung Sudewa (MultiTech Publisher, 2023)
This research aims to determine the response to the concentration of liquid organic fertilizer from citrus fruit waste (LB) in the intercropping pattern between Siamese orange plants as staple crops and annual plants, namely cabbage and chili peppers (T), through the leisa system. This research is field research carried out in Bayung Gede Village, Kintamani District, Bangli Regency from March to December 2023. This research used a Randomized Group Design (RAK) with 2 factors arranged factorially. The first factor tried was liquid organic fertilizer from citrus fruit waste which consisted of 3 levels, namely LB0 (Control = 0 lt/plant), LB1 (2 lt/plant) and LB2 (4 lt/plant), while the second factor tried was the intercropping pattern. (T) which consists of 3 levels, namely T0 (without intercropping), T1 (intercropping Siamese oranges with cabbage plants), T2 (intercropping Siamese oranges with chili plants), so there are 9 treatment combinations, each repeated 3 times so that there are 27 trees. Each one is required. From the results of observations made on the intercropping pattern of Siamese Lombok oranges, the results were not significant for the intercropping pattern of Siamese oranges with cabbage, but it was significantly different from the control, namely 289 fruits/plant, the formation of Fruit-set of 145 fruits/plant increased by 99.31